2023
DOI: 10.1111/pce.14637
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulates mitochondrial biogenesis in plants

Abstract: The site of nitric oxide (NO) production in mitochondrial cytochrome c oxidase and the role of NO in mitochondrial biogenesis are not known in plants. By imposing osmotic stress and recovery on Arabidopsis seedlings we investigated the site of NO production and its role in mitochondrial biogenesis. Osmotic stress reduced growth and mitochondrial number while increasing NO production. During the recovery phase the mitochondrial number increased and this increase was higher in wild type and the high NO‐producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…Similarly, monocotyledonous and dicotyledonous plants have their own independent and intersecting branches (Figure S6), which is consistent with previous research [3]. Interestingly, among widely expressed VQ genes, we found that four genes (GbVQ3, GbVQ12, GbVQ33, and GbVQ34) in Ginkgo biloba, one gene (TcVQ2) in Taxus chinensis, and three genes (PtVQ29, PtVQ30, and PtVQ58) in Pinus tabulaeformis were clustered with AtVQ14, AtVQ9, and AtVQ5 (Figure S6), which were reported as influencing seed development, mediating salinity stress responses, and regulating plant defense, respectively [5,22,26]; three genes (GbVQ26, GbVQ27, and GbVQ29) found in Ginkgo biloba, three genes (TcVQ13, TcVQ14, and TcVQ15) in Taxus chinensis, and three genes (PtVQ37, PtVQ38, and PtVQ39) in Pinus tabulaeformis were clustered with AtVQ22, AtVQ27, and AtVQ28 (Figure S6), which are related to plant defense and growth [18,48,49]. Among them, GbVQ29, TcVQ13, and PtVQ38 are the only VQ genes in the collinear block shared by these gymnosperms, which indicates that these genes have a very conservative, important role and status in seed plants.…”
Section: Phylogenetic Analysis Of Vq Genesmentioning
confidence: 99%
“…Similarly, monocotyledonous and dicotyledonous plants have their own independent and intersecting branches (Figure S6), which is consistent with previous research [3]. Interestingly, among widely expressed VQ genes, we found that four genes (GbVQ3, GbVQ12, GbVQ33, and GbVQ34) in Ginkgo biloba, one gene (TcVQ2) in Taxus chinensis, and three genes (PtVQ29, PtVQ30, and PtVQ58) in Pinus tabulaeformis were clustered with AtVQ14, AtVQ9, and AtVQ5 (Figure S6), which were reported as influencing seed development, mediating salinity stress responses, and regulating plant defense, respectively [5,22,26]; three genes (GbVQ26, GbVQ27, and GbVQ29) found in Ginkgo biloba, three genes (TcVQ13, TcVQ14, and TcVQ15) in Taxus chinensis, and three genes (PtVQ37, PtVQ38, and PtVQ39) in Pinus tabulaeformis were clustered with AtVQ22, AtVQ27, and AtVQ28 (Figure S6), which are related to plant defense and growth [18,48,49]. Among them, GbVQ29, TcVQ13, and PtVQ38 are the only VQ genes in the collinear block shared by these gymnosperms, which indicates that these genes have a very conservative, important role and status in seed plants.…”
Section: Phylogenetic Analysis Of Vq Genesmentioning
confidence: 99%